Unusual Presentation of Type 1 Idiopathic Macular Telangiectasia - Zaïnab Bentaleb Machkour; Philippe Denis; Laurent Kodjikian (Case Reports in Ophthalmological Medicine)
Purpose. To report unusual presentation of type 1A idiopathic macular telangiectasia (IMT). Methods. Two middle-aged women with bilateral IMT were examined. Results. Both patients presented with a gradual vision loss in both eyes. Fundus examination was unremarkable in one case and showed small macular telangiectasia in both eyes in the other case. Fluorescein angiography (FA) revealed early bilateral macular punctuated hyperfluorescence corresponding to the dilated capillaries in both cases. FA and fundus examination confirmed also the absence of vascular abnormalities in the middle or anterior fundus periphery in one case. Spectral-domain optical coherence tomography (SD-OCT) showed cystoid macular edema in both cases. No signs of retinal vein occlusions were detected in both cases and other differential diagnoses were excluded. Based on these findings, the patients were diagnosed with bilateral type 1A IMT according to Gass and Blodi classification and were treated with intravitreal antivascular endothelial growth factor (anti-VEGF) injections and focal laser photocoagulation. Twelve months later, SD-OCT revealed partial regression of the exudative signs and significant VA improvement. Conclusion. We described two patients with an unusual presentation of type 1A IMT with bilateral presentation, affecting two middle-aged women, with occult and without peripheral involvement in one case. The description of more cases of bilateral type 1 IMT should be helpful to more precisely define the pathophysiologic mechanism that could be different from a localized Coats’ disease of the macula area.